Public Sector Shock The Impact of Policy Retrenchment in Europe - Vaughan-Whitehead, Daniel (Edward Elgar Publishing, 2013)
After a first series of policy responses to the 2008-09 crisis aimed at sustaining domestic demand through expansionary anti-crisis packages, most European governments - starting with Greece, Ireland, Bulgaria and Romania, and followed by many others - have since put in place a series of restrictive budgetary policies aimed at reducing their budget deficits. With these new policies, a significant number of jobs and wages have been cut in the public sector. A number of expenditure items related to education and training have also been cut. These reforms have given rise to waves of protest throughout Europe. The goal of this volume is to study this 'public sector shock'. While budgetary reforms seek to ensure a more balanced and sound economic policy, they may generate new work inequalities among public sector employees, most particularly among women, who account for a considerable proportion of public sector employment. Cuts in education and training may also have an impact on the quality of human capital in both the public and private sectors, despite the fact that the recent crisis has shown the value of education as employees with better skills and training are more likely to maintain their jobs and incomes. The authors explore a number of questions, including: what types of reform have been implemented in the public sector and what are their implications in both the short and long term? On the economic side, what will be the impact on wages, and on job quantity and quality? On the social side, what will the effects be on inequality and social cohesion? And what will be the outcome for, and potential role of, social partners and social dialogue? On the basis of a comparative and comprehensive assessment, illustrated by case studies in education, health and public administration, policy issues are discussed with the aim of finding the right mix of public sector reforms.